2023
DOI: 10.1111/avsc.12713
|View full text |Cite
|
Sign up to set email alerts
|

Soil seed bank development of smoke‐responsive plant species in a 23‐year restoration chronosequence and implications for resilience to fire

Abstract: Aims:Responses of ecological restoration projects to disturbances are rarely explored, yet their capacity to withstand and recover from disturbance (resilience) is a critical measure of restoration success. In many plant communities, the soil seed bank (SSB) provides an important source of propagules for species persistence and community resilience to disturbance. Understanding how SSBs develop with time can inform restoration of resilient ecosystems. Here, in fire-prone Banksia woodland restoration following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…While we cannot be certain of the age of the resprouting plants, it is most likely that individuals recruited from seeds during the topsoil application processes which can trigger germination of these smoke‐responsive species (Dixon et al., 2009). While low levels of inter‐fire recruitment of these species do occur (Cowan et al., 2023), seedling establishment is limited (Stevens et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot be certain of the age of the resprouting plants, it is most likely that individuals recruited from seeds during the topsoil application processes which can trigger germination of these smoke‐responsive species (Dixon et al., 2009). While low levels of inter‐fire recruitment of these species do occur (Cowan et al., 2023), seedling establishment is limited (Stevens et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cowan et al. (2023) found that the resilience of restored sites to disturbances such as fire increased with restoration age. The 2023 articles also continued to explore the reintroduction of plant species to degraded sites, highlighting the enduring challenges associated with restoring various species.…”
Section: Reflectionmentioning
confidence: 99%
“…In 2023, articles published in Applied Vegetation Science explored longer-term trajectories and showed a notable shift towards a more comprehensive examination of restoration success and the resilience of restored sites over decadal scales. For example, Cowan et al (2023) found that the resilience of restored sites to disturbances such as fire increased with restoration age. The 2023 articles also continued to explore the reintroduction of plant species to degraded sites, highlighting the enduring challenges associated with restoring various species.…”
Section: Reflec Ti Onmentioning
confidence: 99%